Perlindungan Hukum Terhadap Eksportir Dalam Transaksi Perdagangan Internasional Dengan Menggunakan Metode Pembayaran Konsinyasi (Consignment). - Haryanto, Irfan; Apriani, Rani (Jurnal Ilmiah Wahana Pendidikan, 2025)
International trade or export-import is one of the important elements in the era of globalization in supporting a country's economy. In carrying out international trade activities, especially export activities, legal protection is needed for exporters as sellers in carrying out their business activities because of the many risks that will be accepted by them. Exporters if they carry out international trade activities using a consignment payment system. Normatively, international trade activities, especially exports, have rules that are in line with the Civil Code that applies in Indonesia, but there are also other legal provisions, both national and international legal provisions that can be used as a reference by exporters as sellers in carrying out their business in order to obtain guaranteed legal protection. which is further regulated in Law Number 7 of 2014 concerning Trade and the Convention on the Law Applicable to International Sale of Goods 1955, but this international law convention states in article 1 that this convention only applies to the international sale and purchase of goods, and This convention also only applies to sales and purchases that are stated in written documents or written contracts. This means that in relation to this matter, in order for exporters to obtain legal protection, they are required to carry out their business activities in international trade by making written agreement documents or sales contracts as detailed and perfect as possible starting from the quantity of goods being bought and sold, payment times and deadlines as well as methods for resolving disputes. which will be chosen to be taken if there is a default from the importer as the buyer.